2018
DOI: 10.1111/imr.12650
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐resident memory T cells in tissue homeostasis, persistent infection, and cancer surveillance

Abstract: A large proportion of memory T cells disseminated throughout the body are non-recirculating cells whose maintenance and function is regulated by tissue-specific environmental cues. These sessile cells are referred to as tissue-resident memory T (T ) cells and similar populations of non-recirculating cells also exist among unconventional T cells and innate lymphocyte cells. The pool of T cells is highly diverse with respect to anatomical positioning, phenotype, molecular regulation and effector function. Nevert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
155
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 274 publications
(669 reference statements)
3
155
0
Order By: Relevance
“…Importantly, the density of T RM cells within the tumor environment has been shown to predict for improved survival in a number of cancer types, including advanced‐stage melanoma . In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models . Furthermore, we have recently demonstrated that T RM cells can promote cancer‐immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time .…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Importantly, the density of T RM cells within the tumor environment has been shown to predict for improved survival in a number of cancer types, including advanced‐stage melanoma . In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models . Furthermore, we have recently demonstrated that T RM cells can promote cancer‐immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time .…”
Section: Introductionsupporting
confidence: 59%
“…The population of tumor‐associated lymphocytes in many advanced cancers contains CD8 + T cells that express transcriptional hallmarks of tissue‐resident memory T (T RM ) cells, including a lack of expression of the transcription factor, Kruppel‐like factor 2 and, consequently, an absence of tissue‐exit receptors such as S1PR1 and CCR7 . T RM cells are sessile cells that permanently reside within tissues without recirculating around the body . In the epidermal layer of skin and other epithelial tissues, T RM cells commonly express surface markers such as CD69 and CD103 which discriminate them from recirculating memory T cells .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T RM have limited recirculation out of tissues and serve as sentinels at sites of potential reinfection, where they coordinate the initial response to pathogens and provide a substantial boost to tissue immunity via direct antigen recognition and recruitment of circulating immune cells . The majority of studies on T RM have focused on CD8 + tissue‐resident lymphocyte differentiation, survival and function, while less is known about their CD4 + counterparts, which are also known to mediate antiviral responses . The relationship between circulating and tissue‐resident CD4 + memory T‐cell origins and T H effectors subsets is currently unknown.…”
Section: Introductionmentioning
confidence: 99%